PKM KELOMPOK USAHA IBU RUMAH TANGGA KELURAHAN LAKARSANTRI KOTA SURABAYA - Rizqiawan, Hendrik; Novianto, Iful; Subaderi, Subaderi (Universitas katolik Musi Charitas, 2020)
This Community Service Activity (PKM) has a partner who is a housewife business group locatedin Lakarsantri Village, Lakarsantri District, Surabaya City. The snack product produced andmarketed by partners is Semanggi Stick. However, there are several problems faced by partnerswhile running their business. PKM activities in the form of training, mentoring and accompaniedby the procurement of equipment aim to assist partners in overcoming several problems, includingin the production process, labeling, packaging, business management, and marketing. Of course,by overcoming these problems, there is an increase in the skills, productivity and quality of partnerproducts. This can be seen from the increase in production capacity, where partners are able toproduce 6 to 8 recipes per week from an average of 2 recipes at the same time. Current partnerproducts are also able to last more than 1 month, which previously only has a maximum durabilityof 2 weeks.